(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
The IAEA Safety Guide RS-G-1.2 recommends that occupational radiation monitoring should be implemented whenever it is likely that committed effective doses from annual intakes of radionuclides would exceed1mSv. This study presents the analysis of IAEA methodology for the evaluation of the need for the implementation of an internal monitoring program; considering that it should be carried out whenever the potential internal exposure of incorporation leads to a value of annual committed effective dose equal or higher than 1 m Sv. The IAEA criteria applied to commonly used radionuclides in nuclear medicine, taking into consideration usual manipulated unsealed radioactive sources and handling conditions. It is concluded that the handling of unsealed radioactive sources presents the risk of internal radiation exposure to the workers, requiring the implementation of an internal dosimetry program by the concerned Nuclear Medicine Institutes/Centers. Bangladesh J. Nuclear Med. 20(1): 51-55, January 2017